Association of Peri-ictal MRI Abnormalities With Mortality, Antiseizure Medication Refractoriness, and Morbidity in Status Epilepticus. (28th February 2023) - Bonduelle, Thomas; Ollivier, Morgan; Trin, Kilian; Thomas, Benjamin; Daubigney, Antoine; Michel, Veronique; De Montaudouin, Marie; Marchal, Cécile; Aupy, Jérôme
Abstract : Background and Objectives: Status epilepticus (SE) is a life-threatening emergency requiring a prompt assessment of patient prognosis to guide management. MRI allows the identification of peri-ictal MRI abnormalities (PMAs) and provides insight into brain structural modifications induced by SE. However, little is known about the significance of PMA in SE prognosis. The aim of this study was to determine whether PMAs are associated with an increased mortality in SE and to establish the association between PMA and refractoriness to antiseizure medications, complications encountered, and induced morbidity. Methods: We conducted a retrospective observational cohort study including all eligible consecutive patients over 15 years old and hospitalized with SE at Bordeaux University Hospital (France) between January 2015 and December 2019. The primary end point was in-hospital mortality. A dedicated neuroradiologic reassessment was performed, together with a comprehensive medical review assessing baseline characteristics, in-hospital death, SE characterization, drug refractoriness, and following outcome in survivors. Results: Of 307 patients included, 79 (26%) showed PMA related to SE. Demographic, functional status at baseline and median delay between SE onset and MRI examination were similar in the PMA-positive and PMA-negative groups. In-hospital death occurred in 15% (45/307) patients and was significantly higher in the PMA-positive group (27%, 21/79 vs 11%, 24/228; p < 0.001). In multivariate analysis, the presence of PMA (odds ratio [OR] 2.86, 95% CI 1.02–8.18; p = 0.045), together with SE duration (OR 1.01, 95% CI 1.01–1.02; p = 0.007), older age at SE onset (OR 1.05, 95% CI 1.01–1.09; p = 0.013), preexisting ultimately fatal comorbidity (OR 4.01, 95% CI 1.56–10.6; p = 0.004), and acute lesional SE etiology (OR 3.74, 95% CI 1.45–10.2; p = 0.007) were independent predictors associated with in-hospital death. Patients with PMA had a higher risk of refractory SE (71 vs 33%, p < 0.001). Among survivors, delayed-onset epilepsy (40% vs 21%, p = 0.009) occurred more frequently in the PMA-positive group. Discussion: PMA-positive cases had a higher mortality rate in the largest cohort so far to assess the prognosis value of PMA in SE. As a noninvasive and easily available tool, PMA represents a promising structural biomarker for developing a personalized approach to prognostication in patients with SE receiving MRI.